Deconstructing Internet Memes through Semiotic Analysis: Unveiling Myths and Ideologies in Visual and Verbal Signs - Desak Putu Eka Pratiwi; I Komang Sulatra; I Gede Agus Dewangga (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This paper will examine the meanings embedded in memes through semiotic analysis. Semiotics, as proposed by Chandler (2007), is the study of signs and symbols and their meanings, particularly in the context of communication and representation. Internet memes are culturally significant artifacts that consist of visual and verbal signs which convey a shared experience or cultural reference within a community. The objective of this study is to explore the myth and ideology that is conveyed through the signs used in these memes, and to examine the message that is being communicated to the audience. The data were collected by using observation method which involves the selection of a sample of widely shared Internet memes on social media platforms. This study used qualitative method in analyzing the data. These memes were analyzed using semiotic analysis to identify the signs used in the Internet memes and their associated meanings. The findings suggest that memes are a form of communication that uses signifiers to convey a message, and the connotative meanings of these signifiers can reveal the myth and ideology behind the message. Memes convey cultural values and beliefs and can challenge or reinforce dominant cultural ideologies. Understanding them can shed light on cultural reproduction in society, with implications for media, cultural, and sociology studies in the digital age.